2021
DOI: 10.1177/0272989x21998951
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Metastatic Lung Cancer and Oncologists’ Views on Achievement of Treatment Goals and Making the Right Treatment Decision: A Prospective Multicenter Study

Abstract: Background Previous studies have investigated patients’ treatment goals before starting a treatment for metastatic lung cancer. Data on the evaluation of treatment goals are lacking. Aim To determine if patients with metastatic lung cancer and their oncologists perceive the treatment goals they defined at the start of systemic treatment as achieved after treatment and if in hindsight they believe it was the right decision to start systemic therapy. Design and Participants A prospective multicenter study in 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…For example, one study explicitly added some qualitative interviews to elucidate findings in what commenced as an exclusively quantitative study of patients using multiple types of therapy and explicitly reported only one experience clearly attributable to a patient using an immune checkpoint inhibitor. 44 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one study explicitly added some qualitative interviews to elucidate findings in what commenced as an exclusively quantitative study of patients using multiple types of therapy and explicitly reported only one experience clearly attributable to a patient using an immune checkpoint inhibitor. 44 …”
Section: Resultsmentioning
confidence: 99%
“…For example, one study explicitly added some qualitative interviews to elucidate findings in what commenced as an exclusively quantitative study of patients using multiple types of therapy and explicitly reported only one experience clearly attributable to a patient using an immune checkpoint inhibitor. 44 By contrast, several studies reported detailed data on patient experiences, permitting deeply nuanced interpretations. For example, one study 43 systematically sampled patients before treatment, during treatment, after successful treatment, and after treatment failed to prevent disease progression, thematically exploring the experiences of each group.…”
Section: Table 1 Continuedmentioning
confidence: 99%
See 1 more Smart Citation
“…For these patients, treatment is aimed at life extension while improving HRQOL. We recently found that pre-treatment HRQOL goals are only met by less than half of patients [ 3 , 4 ]. In addition, patients with an incurable disease often have a poor prognostic perception, as a result of the efficacy–effectiveness gap [ 25 ], (which can increase) deficient patient–doctor communication, as well as attempts of patients and their relatives to maintain the hope of a cure.…”
Section: Discussionmentioning
confidence: 99%
“…For metastatic NSCLC patients, treatment is aimed at life extension while improving or at least preserving health-related quality of life (HRQOL). Due to the increased availability of treatments, especially when a targetable driver mutation is present, treatment decisions in metastatic NSCLC have become a delicate and complicated process for both the clinician as well as the patient and their relatives [ 3 , 4 ]. Currently, most clinical decisions are based on ‘traditional’ clinical criteria, such as mutational status and TNM stage.…”
Section: Introductionmentioning
confidence: 99%